Use of LSPR Spectroscopy Biosensing for In Situ Identification of Arsenic from Bioleaching of Realgar by Acidithiobacillus ferrooxidans - Xu, Ruixiang; Zhao, Wenbin; Xu, Shenghui; Yan, Lei; Wu, Zhengrong; Liu, Yuheng; Ma, Wantong; Chen, Peng (Journal of Spectroscopy, 2018)
Localized surface plasmon resonance (LSPR) spectroscopy has received extensive attention as a new method in chemical and biological analysis that can be integrated with nanotechnology. As a new analytical method, LSPR possesses various advantages over the traditional bioanalysis method of enzyme-linked immunosorbent assay (ELISA), including a label-free procedure, low cost, high response speed, simple operation and structure, and ease of storage and transport. Additionally, in situ and high-throughput measurements can be achieved. This study aims to solve the problem of the lack of in situ and highly efficient monitoring methods for current realgar bioleaching processes. An LSPR chip is made to monitor the changes in arsenic content in the process of realgar bioleaching. A convenient, fast, sensitive, and high-throughput method of bioleaching process investigation based on the LSPR spectroscopic in situ monitoring technique is proposed. The LSPR chip provided a highly specific selectivity and a linear detection of arsenic content in the range of 1.0–100.0 μM with detection limit (LOD) 0.898 μM. The developed chip was applied to the quantification of realgar bioleaching sample with satisfactory results.